Photovoltaic solar energy and sustainability in higher education institutions: a multiple case study - Barbosa Soares, Cícero Allan; de Nadae, Jeniffer; do Nascimento, Diego Coelho; Alves Firmino, Paulo Renato; Morioka, Sandra Naomi (Revista Gestão da Produção Operações e Sistemas, 2023)
Purpose: to identify which Higher Education Institutions (HEIs) in the Metropolitan Region of Cariri (MRC) use photovoltaic solar energy, then analyze the sustainability measures used by the HEIs, correlating them with the Sustainable Development Goals (SDG). Design/methodology/approach: a case study, where the secondary data source and the data analysis technique is bibliographic and documentary. Findings: four HEIs use photovoltaic solar energy (22.22%) in the MRC from a total of 18 HEIs, revealing a predominance of public HEIs (75%) over private HEIs (25%). The systems are new and have been installed within the last five years. The simple average payback found is 4.9 years. The study showed that in other universities worldwide, this period varies from 3 to 14.29 years. Average monthly energy generation ranges from 18,000 kWh to almost 115,000 kWh. Sustainable Development Goal 7 was observed in all the HEIs in the study, with 1 of the HEIs using measures found in all the SDGs. Research, practical and social implications: Results reveal that the major motivation for implementing photovoltaic solar energy in these HEIs is environmental and social, and not economic, also revealing the predominance of public HEIs over private HEIs. Since it is a region with a high potential to use renewable energy, the results found are also intended to encourage debate among the other HEIs identified in the study and for them to adopt this solution. Originality/value: HEIs has an enormous capacity to have a positive influence on society and is a bridge between research, practice, and knowledge dissemination. The MRC has a large educational structure, with 18 HEIs, and can significantly contribute to meeting the SDG. This article demonstrates the structure and impacts of adopting sustainability measures in these HEIs. Keywords: Sustainable Development; Universities; Renewable Energy; SDG.